عقوبة اﻹعدام في شريعة اﻹسﻼم - Siti Maheran (PERADA, 2019)
The death penalty has become an inseparable part of the studies of law, both in eastern and western countries. At the time, the number of crimes or atrocities is keeping increased, and the offenders are not deterrent after completing their sentences. In order to provide accurate results, this study used data analysis methods, from various sources of Islamic law, and the works of Islamic scholars, such as Imam Abu Hanifah, Imam Malik, Imam Shafi’I and Imam Ahmad bin Hanbal. This dtudy provides of scientific certainty that the death penalt in Islam has a strong foundation of the highest sources of Islamic law, namely the Quran and Sunnah, and is supported by the implementation of the law during the reign of Abu Bakr, Umar, Utsman and Ali and the caliphs after them. The application of penalties, such as the Qisas, Hudud and Ta’zir (ijtihad), is implemented by the legal government, according to the offense.